Access to Psychological Support for Young People Following Stoma Surgery: Exploring Patients' and Clinicians' Perspectives. (February 2021) - Polidano, Kay; Chew-Graham, Carolyn A.; Farmer, Adam D.; Saunders, Benjamin
Psychological problems are common among people with inflammatory bowel disease (IBD) following stoma surgery. However, the ways in which stoma-related psychological needs are identified and addressed in health care settings remain unexplored. In this study, we investigated the perspectives of young people with a stoma and health care professionals about access to psychological support. Semi-structured interviews were conducted with young people with an IBD stoma (18–29 years, n = 13) and health care professionals ( n = 15), including colorectal surgeons, gastroenterologists, specialist nurses in IBD and stoma care, and general practitioners in England. Data collection and analysis were informed by constructivist grounded theory. Three analytic categories were developed: "initiating support-seeking, " "affirming psychological needs, " and "mobilizing psychological support, " which capture young peoples' trajectory to access psychological support. Based on the findings, we highlight the need for both patients and health care professionals to assign greater priority to the identification of psychological symptoms post-stoma surgery. More effective care pathways, which include responsive psychological services, would enhance access to psychological support for young people with a stoma.